2015
DOI: 10.1063/1.4913556
|View full text |Cite
|
Sign up to set email alerts
|

Specific interactions between DNA and regulatory protein controlled by ligand-binding: Ab initio molecular simulation

Abstract: Abstract. The catabolite activator protein (CAP) is one of the regulatory proteins controlling the transcription mechanism of gene. Biochemical experiments elucidated that the complex of CAP with cyclic AMP (cAMP) is indispensable for controlling the mechanism, while previous molecular simulations for the monomer of CAP+cAMP complex revealed the specific interactions between CAP and cAMP. However, the effect of cAMP-binding to CAP on the specific interactions between CAP and DNA is not elucidated at atomic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This observation corroborates earlier experimental studies that showed significant changes in the locations and interactions of residues in the phosphate-binding cassette (residues GLY-71 to ALA-84) of CAP upon binding of cAMP . In particular, ARG-82 broke its salt bridge with GLU-129 and entered into the cAMP-binding pocket to establish a new salt bridge with the phosphate unit of cAMP. ,, In addition, two other salt bridges involving GLU-77, GLU-78, and ARG-122 were broken, and a new salt bridge was formed between ARG-122 and GLU-129 after cAMP binds to CAP …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This observation corroborates earlier experimental studies that showed significant changes in the locations and interactions of residues in the phosphate-binding cassette (residues GLY-71 to ALA-84) of CAP upon binding of cAMP . In particular, ARG-82 broke its salt bridge with GLU-129 and entered into the cAMP-binding pocket to establish a new salt bridge with the phosphate unit of cAMP. ,, In addition, two other salt bridges involving GLU-77, GLU-78, and ARG-122 were broken, and a new salt bridge was formed between ARG-122 and GLU-129 after cAMP binds to CAP …”
Section: Resultssupporting
confidence: 90%
“…84 In particular, ARG-82 broke its salt bridge with GLU-129 and entered into the cAMP-binding pocket to establish a new salt bridge with the phosphate unit of cAMP. 58,85,86 In addition, two other salt bridges involving GLU-77, GLU-78, and ARG-122 were broken, and a new salt bridge was formed between ARG-122 and GLU-129 after cAMP binds to CAP. 37 The F-helices have zero interaction with the cAMP molecules in the cAMP-CAP complex due to the lack of direct contact between them.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation